External Stenting (Exostenting) to Correct Vascular Torsion and Angulation - Silva, Michael B., Jr; Shoaib, Muhammad; Miyara, Santiago J.; Guevara, Sara; McCann-Molmenti, Alexia; Silva, H. Colleen; Watt, Stacey; Zafeiropoulos, Stefanos; Hayashida, Kei; Takegawa, Ryosuke; Shinozaki, Koichiro; Choudhary, Rishabh C.; Cho, Young Min; Kressel, Adam M.; Alsalmay, Yaser M.; Grande, Daniel A.; Cicalese, Luca; Aranalde, Gabriel I.; Covelli, Grace; Becker, Lance B.; Shore-Lesserson, Linda; Molmenti, Ernesto P. (International Journal of Angiology, 2021)
Organ transplantation can be associated with vascular torsions and angulations of both recipient and donor vessels. Such kinks and/or torsions of vessels can compromise the vascular integrity, obstruct inflow and/or outflow, and result in loss of the organ and/or body parts. On many occasions, mild angulations and torsions can be successfully addressed by repositioning the organ. In cases where the abnormal findings persist, maneuvers such as placing a fat pad to create a smoother curve, or even opening the peritoneum (in the case of kidney transplants) to allow for a better positioning of the organ, are associated with successful outcomes. When such torsions/angulations persist despite these approaches, further innovative tactics are required. In the current report, we propose a technique that involves longitudinally opening of a synthetic graft that is rigid enough to maintain its shape, such as a ringed polytetrafluoroethylene graft, and placing it as an external stent around the angulated/torsioned vessel. This maneuver will correct the underlying vascular compromise without having to perform any further invasive interventions, such as reimplanting the organ or resecting part of the involved vessel. Although primarily illustrated for application by describing an instance in which exostenting was applied during kidney transplantation, our approach could be applied to any vessel under many circumstances where angulations/twists are encountered. In this report, we describe the use of an external stent, also called exostenting, to correct a severe torsion/angulation of the external iliac artery in a kidney transplant recipient where all other measures were unsuccessful.
Keywords: vascular; torsion; vessel; tortuosity; external stenting; exostenting; support; organ compromise; transplant; kidney